Índice de morosidad según tipo y modalidad de crédito de la banca múltiple en el Perú, periodo 2019 – 2023 - Carranza del Aguila, Bill Patrik (2025)
The objective of the research was to determine the Commercial Banking index in its different lines of credit in the period 2019 - 2023. The research is basic, with a quantitative approach at a descriptive and cross-sectional level; The investigation concludes that the delinquency rate of the Commercial Bank of Peru, in the period 2019 - 2023, has been increasing except for the year 2021 where it decreased from 3.80% in 2020, went to 3.77% in 2021, and subsequently rose to 3.95% in 2022 and end 2023 with 4.31%; The lowest of the indexes is in 2019 with only 3.02%. The highest delinquency rates are in medium and small companies with high qualification levels, influenced by credit cards, promissory notes and financial leasing. The indices in the low category are large companies; Consumer and mortgage loans are at a low and acceptable level in the study period.